Current understanding and implementation of ‘care navigation’ across England: a cross-sectional study of NHS clinical commissioning groups - Tierney, S; Wong, G; Mahtani, K (Royal College of General Practitioners, 2019)
Background: Care navigation is an avenue to link patients to activities or organisations that can help address non-medical needs affecting health and well-being. Understanding of how care navigation is being implemented across primary care is lacking. Aim: To determine how ‘care navigation’ is interpreted and implemented currently by clinical commissioning groups (CCGs). Design and Setting: A cross-sectional study involving CCGs in England. Method: A questionnaire was sent to all CCGs, inviting them to comment on who provides care navigation, for which patients, how individuals are referred and whether services are being evaluated. Responses were summarised using descriptive statistics. Results: We received useable responses from 83% of CCGs (n=162) and over 90% had some form of care navigation running in their area. 75 different titles were used to describe the role. Most services were open to all adult patients, although particular groups may be targeted (e.g. older people, those with a long-term condition). Referrals tended to be made by a professional, or people were identified by a receptionist when they presented to a surgery. Evaluation of care navigation services was limited. Conclusion: There is a policy steer to engaging patients in social prescribing, using some form of care navigator to help with this. Our data highlights that although this type of role is being provided, its implementation is heterogeneous. This could make comparison and the pooling of data on care navigation difficult. It may also leave patients unsure about what care navigation is about and how it could help them.